2020
DOI: 10.9734/jammr/2020/v32i230369
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Infection and Biomarkers Correlates of Liver Injury among Healthy Blood Donors in Nigeria

Abstract: Objectives: Destruction of blood cells and damage to hepatocytes are the hallmark of hepatitis B viral infection. This cross-sectional study was undertaken to evaluate some hematological parameters and biomarkers of liver injury in healthy blood donors infected with the occult and overt hepatitis B attending the University of Abuja Teaching Hospital (UATH) and Nnamdi Azikiwe University Teaching Hospital (NAUTH) Nnewi, Nigeria. JAMMR, 32(2): 69-78, 2020; Article no.JAMMR.54812 70 Materials and Methods: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
6
1
2
Order By: Relevance
“…Theo một nghiên cứu công bố năm 2020 của tác giả Ahaneku Iherue Osuji và cộng sự tại Nigeria tiến hành trên 100 mẫu máu từ người hiến máu có xét nghiệm âm tính với HBsAg và các dấu ấn chẩn đoán viêm gan siêu vi B, người ta phát hiện 3 mẫu có HBV-DNA dương tính (3%). Trong nghiên cứu về nhân khẩu học xã hội, người ta đã chỉ ra rằng người hiến máu là nam có tỷ lệ nhiễm HBV cao hơn người hiến máu là nữ [5].…”
Section: Bàn Luậnunclassified
See 1 more Smart Citation
“…Theo một nghiên cứu công bố năm 2020 của tác giả Ahaneku Iherue Osuji và cộng sự tại Nigeria tiến hành trên 100 mẫu máu từ người hiến máu có xét nghiệm âm tính với HBsAg và các dấu ấn chẩn đoán viêm gan siêu vi B, người ta phát hiện 3 mẫu có HBV-DNA dương tính (3%). Trong nghiên cứu về nhân khẩu học xã hội, người ta đã chỉ ra rằng người hiến máu là nam có tỷ lệ nhiễm HBV cao hơn người hiến máu là nữ [5].…”
Section: Bàn Luậnunclassified
“…Theo đó, tập trung nhiều ở đối tượng nghiên cứu có giới tính nam trong độ tuổi từ 46-60 tuổi, được chứng minh qua phép kiểm định Fisher's exact với giá trị p có ý nghĩa thống kê (Bảng 5). Kết quả này có sự tương đồng về giới tính nam chiếm tỷ lệ cao với các nghiên cứu của các tác giả ngoài nước được trình bày ở trên như A.Jary, Ahaneku Iherue Osuji, Pierre Cappy, Sanaba Boumbaly, Danxiao Wu [4][5][6][7][8] và có sự tương đồng về nhóm người lớn tuổi chiếm đa số với nghiên cứu của tác giả Danxiao Wu và cộng sự tại Chiết Giang, Trung Quốc [8]. Điều này có thể bước đầu nhận xét rằng nam giới do nhiều yếu tố tác động chủ quan và khách quan khác nhau như đặc thù công việc, thói quen, phong cách sống …nên có thể có nhiều nguy cơ nhiễm HBV hơn nữ.…”
Section: Bàn Luậnunclassified
“…This automated ampli cation and quanti cation have a detection limit of between 20-170,000,000 IU/mL. Sample preparations and polymerase chain reaction (PCR) ampli cation were performed according to the method described by Osuji et al [9]. The Standard Operating procedures were strictly followed to ensure accurate laboratory ndings following the manufacturer's instructions.…”
Section: Determination Of Alanine Amino Transferase (Alt)mentioning
confidence: 99%
“…In acute HBV infection, there is usually an increase in aminotransferases, especially the ALT level, from a moderate to an astronomical increase of more than 100 folds. Chronic HBV infection however usually presents with normal or elevated ALT levels of up to 200 IU/L in about 90% of patients [3,8,9]. Therefore, the varying severity of hepatitis and other liver diseases associated with various stages of HBV infection, including the acute and chronic stages, may also produce varying degree of abnormal haematological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hematological abnormalities are among the most frequently recognized extrahepatic irregularities observed at the time of diagnosis [18]. White blood cell (WBC) and red blood cell (RBC) counts and platelet (PLT) parameters are included in the complete blood count and are associated with certain actions [19]. A study by [18] and [20] reported that viral hepatitis has a role in altering the functions and values of these parameters.…”
Section: Introductionmentioning
confidence: 99%